Biomass Production and Prediction Models for Acacia nilotica in Salt Affected Vertisols in Karnataka - Raizada, A.; Rama Mohan Rao, M. S.; Nambiar, K. T. N.; Padmaiah, M. (Indian Forester, 2007)
Biomass prediction models were prepared for 17 year old Acacia nilotica trees raised on salt affected vertisols of the semi arid tropics in Karnataka. A. nilotica was raised at 8Ã—8 m spacing with an under storey of three grass species - Cenchrus ciliaris, Dicanthium annulatum and Chloris bourneii for the production of fodder. Wide variations occurred in the trees sampled by random selection in the plantation, with respect to diameter (3.1 to 16 cm) and tree height (3.5 to 5.1 m). Leaf biomass varied from 0.5 to 3.1 kg/tree, contribution by big branches (> 2 cm dia.) varied from 3.81 to 24.13 kg/tree. Total above ground biomass ranged from 26.5 to 100.74 kg/tree. Prediction models with the best fit were in the linear form with r2 values of 0.8261, 0.9162 and 0.8665 for predicting bole, utilizable and total above ground biomass.